Analysis of The Influence of Work Environment, Work Motivation, Work Discipline on Job Satisfaction and Employee Performance (Case Study at the Regional Secretariat of Ponorogo Regency) - Wahyu Dwi Kuncoro; Riawan Riawan (Dinasti Review, 2025)
This study aims to analyze the influence of a comfortable and safe work environment and the existence of motivation and discipline can increase job satisfaction so that it can increase effective work productivity to employee performance